2018
DOI: 10.1007/s00464-018-6301-2
|View full text |Cite
|
Sign up to set email alerts
|

A propensity score-matched analysis of robotic versus open pancreatoduodenectomy for pancreatic cancer based on margin status

Abstract: RPD and OPD achieved the same rate of R1 resections in resectable PC. RPD was also non-inferior to OPD with respect to all secondary study endpoints. Because of the high number of patients required to run a RCT, further assessment of RPD for PC would require the implementation of an international registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
1
25
1
2
Order By: Relevance
“…After sensitivity analysis, the meta-results did not show any reversal changes. However, when Cai et al [14] was eliminated, the heterogeneity was signi cantly reduced (I 2 = 0%, P = 0.43), the xed-effects model yielded an RR of 0.65, 95%CI (0.50, 0.86), P = 0.002, and the statistically signi cant difference remained. In both retrospective and prospective cohort studies, there was a statistically signi cant difference in the number of transfusion between the RPD group and the OPD group (RR = 0.69, 95% CI: 0.48, 0.99, P = 0.04; RR = 0.48, 95% CI: 0.31, 0.75, P = 0.001, respectively) (Figs.…”
Section: Comparison Of Intraoperative Blood Transfusionmentioning
confidence: 95%
See 1 more Smart Citation
“…After sensitivity analysis, the meta-results did not show any reversal changes. However, when Cai et al [14] was eliminated, the heterogeneity was signi cantly reduced (I 2 = 0%, P = 0.43), the xed-effects model yielded an RR of 0.65, 95%CI (0.50, 0.86), P = 0.002, and the statistically signi cant difference remained. In both retrospective and prospective cohort studies, there was a statistically signi cant difference in the number of transfusion between the RPD group and the OPD group (RR = 0.69, 95% CI: 0.48, 0.99, P = 0.04; RR = 0.48, 95% CI: 0.31, 0.75, P = 0.001, respectively) (Figs.…”
Section: Comparison Of Intraoperative Blood Transfusionmentioning
confidence: 95%
“…Six studies [10,13,14,19,20,23] reported the severe complication. There was a low degree of heterogeneity (I 2 = 0%, P = 0.89) among the studies.…”
Section: Severe Complicationmentioning
confidence: 99%
“…A review of our own experience revealed longer operative times of approximately 136 min when compared with our open PD cohort [14] . However, robotic PD resulted in less blood loss (200 mL lower), a shorter intensive care unit stay, a lower 30-day complication rate, and no difference in total costs compared with open PD [15,16] .…”
Section: Discussionmentioning
confidence: 75%
“…Multiple single or multi-institutional retrospective studies to compare specific outcomes between robotic, laparoscopic and open approaches are reported [6,[14][15][16][18][19][20][21][22][23][24] . A large systematic review examined data from 13 retrospective series [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four studies were included in the final quantitative data synthesis, totaling 12,579 patients (2,175 robotic PD and 10,404 open PD) 8,28,30, . Seven studies 30,34,36,38,41,50,52 were prospective cohort studies and 17 retrospective cohort studies 8,28,35,37,39,40,[42][43][44][45][46][47][48][49]51,53,54 . In four of these studies 34,40,43,50 , data were extracted from the abstracts of conference proceedings published in indexed journals.…”
Section: Discussionmentioning
confidence: 99%